DIVERSIFICATION, CEO COMMITMENT, AND FIRM PERFORMANCE - Silalahi E. Engelbertha; Bimo Dwinanto Irenius (Dynamic Relationships Management Journal (DRMJ), 2021)
This study examined the effect of diversification strategies on firm performance and the extent to which the chief ex‐ ecutive officer (CEO) commitment moderates this relationship. The effect of diversification on firm performance was analyzed in a sample with both above‐average and below‐average diversification levels. The sample consisted of 76 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2007 to 2018, which were analyzed using panel data regression with a balanced panel. Tobin’s Q was utilized to measure firm performance, compounded with three measures of diversification strategies: entropy index, Herfindahl index, and the number of segments. The results show that diversification leads to lower firm performance, whereas CEO commitment eliminates the negative influence of diversification on company performance in all measurement models (i.e., entropy, Herfindahl index, and the number of segments). Accordingly, the negative effect of diversification strategies and consistent CEO commitment were ob‐ served among the samples with high and low diversification levels.